Pengaruh Komunikasi Internal dan Motivasi Kerja terhadap Semangat Kerja Karyawan pada PT. BPR Dewata Candradana - Putri, Ida Ayu Laksmi; Wimba, MM, I Gusti Ayu; Dewi, Ida Ayu Sasmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The term "morale" refers to the sentiments that people or groups have when they are deeply happy with policies, careers, working conditions, collaboration, and the work environment. These feelings motivate people to do their best job more productively. positive or negative. Morale is influenced by many factors such as internal communication and work motivation. The formulation of the problem and the objectives of this study are to determine the effect of internal communication and work motivation on employee morale at PT. BPR Dewata Candradana.The location of this research is at PT. BPR Dewata Candradana and the sample used in The saturated sample method was used to select 40 respondents for this investigation. Validity, reliability, conventional assumptions, multiple linear regression, coefficient of determination, t-test, and F-test are among the data analysis methods employed in this study.Based on the results of the study it can be seen that: (1) Internal communication has a positive and significant effect on employee morale with a tcount = 2.741 and a sig value of 0.009. (2) Work motivation has a positive effect on employee morale with a value of 2.880 compared to a sig value of 0.007. (3) Internal communication and work motivation have a positive effect on employee morale. The magnitude of the independent variable’s influence on employee morale is 88.0%.